Taking research to non-researchers: the case of a research compendium of BRAC - Ahmed, Hasan Shareef; Ullah, AKM Ahsan; Chowdhury, AMR (BRAC Research and Evaluation Division (RED), 2020)
The study assessed the readership of Nirjash, a vernacular research compendium of BRAC. Since its inception in 1995, five issues have been produced. In 1998 we conducted a readership survey on its usefulness, accessibility, awareness, and readability. Data were collected from 1,698 field staff of 103 BRAC area offices in 18 districts. Of the respondents, 497 were interviewed directly with a questionnaire, but for the rests (1,201) it was self-administered. Findings revealed that 45% of the respondents were aware of Nirjash, and of them 79% had read it. Field managers were more aware of Nirjash (87%) than their junior colleagues (40%) . Among those who have read it, 48% found it easy to read, 7% found it difficult, and 93% reported that they benefited from reading Nirjash. Only four respondents did not like Nirjash at all. Over the first three years, readership increased by 26%. No field office had collection of all the issues of Nirjash reflecting problem in distribution system.